Tin content and sensory properties of canned-pork and beans in lacquered & plain tin cans - Inumerable, Carmen B.
This study aimed to determine the effect of the type of can and length and temperature of storage on the tin content and attributes of pork and beans, specifically its flavor and general acceptability. Samples were packed into lacquered (C-enamel) and plain tin cans and analyzed at certain intervals. Tin content was determined using stomic absorption spectophotometry. The results of the tin content analysis and visual examination of the can interior showed that lacquered cans were effective in terms of corrosion prevention. The tin content in plain tin cans rose up to 62 ppm after 2 months' storage, while for lacquered cans, it was only about 39 ppm. However, the results of the sensory evaluation revealed that samples from plain tin cans were significantly more acceptable than those from lacquered cans. The product packed in lacquered cans had bitter flavor which affected its acceptability.